Geographic Information System for Data Collection of Cooperatives and Small Medium Enterprises in East Sumba - Sasqia Adinda Amin; Fajar Hariadi2s; Erwianta Gustial Radjah (Yayasan Kita Menulis, 2025)
Cooperatives and Small and Medium Enterprises (SMEs) are important pillars in the regional economy, with the Cooperatives and SMEs Office playing a crucial role in its development. East Sumba Regency has great potential, but the lack of comprehensive spatial data hinders the making of appropriate policies. This research aims to develop a Geographic Information System (GIS) for data collection of Cooperatives and SMEs in East Sumba Regency. The research method used is waterfall, with data collection through interviews, observations, and documentation. The results are in the form of maps and information on the distribution of Cooperatives and SMEs. It is hoped that this GIS can assist the Agency and Regional Governments in formulating policies that are right on target, as well as supporting training and funding. The positive impacts of GIS include improved data accuracy and quality, transparency, and accountability in the development of Cooperatives and SMEs. The System Usability Scale (SUS) method provides a positive picture of user satisfaction, with an average score of 90 indicating the